Search for a charged partner of the X(3872) in the B meson decay B -> X-K, X--> J/psi pi(-)pi(0) - Aubert, B; Barate, R; Boutigny, D; Couderc, F; Karyotakis, Y; Lees, J; Poireau, V; Tisserand, V; Zghiche, A; Grauges-Pous, E; Palano, A; Pompili, A; et al. (2005)
We search for a charged partner of the X(3872) in the decay B → X - K, X- → J/ψπ-π0, using 234 × 106 BB events collected at the Y(4S) resonance with the BABAR detector at the PEP-II e+e- asymmetric-energy storage ring. The resulting product branching fraction upper limits are B(B 0 → X- K+, X- → J/ψπ-π0) < 5.4 × 10-6 and B(B- → X-K̄0, X- → J/ψπ-π0) < 22 × 10-6 at the 90% confidence level. © 2005 The American Physical Society.